Monimuotoinen ansiotyö Näkökulmia monista lähteistä ansaintaan - Haapakorpi, Arja (Tampere University Press, 2022)
This edited volume discusses multiple job holding as part of Finnish working life. The articles in this book examine this little researched phenomenon through a wide range of empirical data. Based on Statistics Finland's register data, different ways of combining jobs are classified. Interview material sheds light on the conditions for holding multible jobs. A new perspective is provided by the chaos theory of careers. According to the results of the study, very different paths lead to becoming a multiple job holder. The combination of jobs is influenced by the life path and interests of the individual, as well as by constraints and opportunities available. Motives can also be linked to professional networks, decisions made by immediate family, coincidences or whims. This book helps to understand the diversity of ways of working. At the same time, it illustrates the challenges faced by those who work multiple jobs as they try to operate within simpler models and categorisations of labour. It is essential reading for anyone interested in the changing nature of work, especially researchers, students and policy-makers.